Effect of laser welding heat input on fatigue crack growth and CTOD fracture toughness of HSLA steel joints - Ribeiro, Henrique Varella; Reis Pereira Baptista, Carlos Antonio; Fernandes Lima, Milton Sergio; Santos Torres, Marcelo Augusto [UNESP]; Marcomini, Jose Benedito (Elsevier B.V., 2021)
High strength low alloy steels are employed in structural elements and, despite presenting good weldability, the welded joint is always a critical issue and its evaluation is fundamental in guaranteeing structural integrity. The mechanical properties of weld beads can be significantly different from the base material & rsquo;s properties due to metallurgical alterations caused by the welding process. One of the factors leading to significant impact is the heat input. This paper evaluates the hardness, fracture toughness and fatigue crack growth in weld beads obtained via a Laser process with two different heat inputs, which resulted in weld beads with distinct microstructures: one composed of ferrite presenting different morphologies and the other composed of martensite and bainite. The aims of this work are evaluating the effect of Laser welding heat input on microstructures in the weld beads, and the correlation of the microstructure with fatigue crack growth and crack-tip opening displacement fracture toughness. Fracture toughness presented itself to be more sensitive to the microstructural alterations caused by the heat input than hardness and fatigue crack growth. Weld beads showed higher resistance to fatigue crack growth when compared to the base metal, even though there were no significant differences between them. (c) 2021 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Laser welding; Fatigue crack growth; Fracture toughness; Welding metallurgy; HSLA steel